RANKING VERSUS AUTHENTIC LEARNING IN COSMETOLOGY, ETHNOBEAUTY, AND WELLNESS EDUCATION: A BEHAVIORIST ANALYSIS OF LEARNING MOTIVATION IN INDONESIA - Raya Eka Ramadhani; M Mamduh Winangun; Sri Usodoningtyas (Adornata : Ethnobeauty and Wellness Journal, 2026)
The ranking system in Indonesian education remains a debated issue, especially amid the shift toward more comprehensive, student-centered, and process-oriented learning. This issue is also relevant in cosmetology, ethnobeauty, and wellness education, where learning outcomes should not only be measured through grades or class rank, but also through practical competence, cultural understanding, creativity, ethical awareness, client-centered care, and sustainable beauty values. This study analyzes the ranking system and authentic learning through the perspective of behaviorist learning theory. The method used in this study is qualitative library research by reviewing journals, books, policy documents, and relevant articles related to behaviorism, motivation, assessment, authentic learning, and beauty vocational education. The findings indicate that the ranking system reflects the application of behaviorism, particularly through stimulus, response, reinforcement, reward, and punishment. In the short term, ranking may encourage discipline and academic performance. However, excessive reliance on ranking can shift students’ motivation from intrinsic understanding to external recognition. In the context of beauty and wellness education, this condition may limit students’ ability to develop reflective practice, cultural sensitivity, natural ingredient literacy, and professional responsibility. Therefore, assessment in cosmetology, ethnobeauty, and wellness learning needs to move beyond ranking toward authentic assessment, portfolio-based evaluation, project-based learning, reflective feedback, and practical demonstrations. Such an approach supports meaningful learning while maintaining the holistic, cultural, and sustainable values required in beauty and wellness education.